Local and Systemic Expression of Immunomodulatory Factors in Chronic Pancreatitis - Komar, Hannah M. (Pancreas, 2017)
Inflammatory and fibrotic events that drive chronic pancreatitis (CP) are likely orchestrated via signaling of soluble cytokines and chemokines systemically and within the pancreas. However, a comprehensive summary of the expression of such factors during CP has not been reported to date. This information is important given continued interest in targeting cytokines that influence CP pathogenesis. Reported data on the expression change of soluble immunomodulatory factors in human CP patients were identified via a literature search using a single search term. Thirty-one articles meeting the pre-specified inclusion criteria were identified to generate a compiled data summary. Compiled data demonstrated up-regulation of several factors in the blood or pancreas microenvironment of CP patients. Nine factors were elevated in both compartments, including fractalkine, interferon gamma (IFN-γ), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), macrophage inhibitory cytokine 1 (MIC-1), neutrophil gelatinase-associated lipocalin (NGAL/LCN2), transforming growth factor beta (TGF-β), and tumor necrosis factor alpha (TNF-α). Most up-regulated factors could be classified into one of several functional groups, including inflammation, chemotaxis, angiogenesis, bone remodeling, extracellular matrix remodeling, and pain. Following further validation, these factors may be used as biomarkers for disease diagnosis, identification of comorbidities, or as potential therapeutic targets.